Uncovering novel exosome-specific miRNA markers and potential molecular mechanisms in autoimmune pancreatitis - Lai, Yamin; Shang, Mengmeng; Yang, Hong; Lv, Hong; Zhang, Panpan; Guo, Tao; Zhang, Wen; Yang, Aiming; Yu, Jia; Qian, Jiaming; Wu, Dong (Genomics (San Diego, Calif.), 2025)
Autoimmune pancreatitis (AIP) is a rare disease and sometimes difficult to make a diagnosis. This study aimed to identify exosomal miRNAs that could serve as novel biomarkers of type 1 AIP. We extracted miRNAs from the exosomes of patients with AIP, chronic pancreatitis (CP), pancreatic cancer, and healthy control individuals. To identify differentially expressed miRNAs (DEmiRNAs) associated with AIP, second-generation sequencing and differential expression analysis were performed. Target gene prediction, immune correlation analysis, functional annotation, and construction of lncRNA-miRNA-mRNA and transcription factor (TF)-miRNA-mRNA networks were then performed. Finally, qPCR analysis and ROC evaluation were performed for hub DEmiRNA. Exosomal miRNAs exhibited specific expression profiles in patients with type 1 AIP. The differentially expressed target genes PLXNA2 and PGM3, and the differentially expressed lncRNA MALAT1 associated with hsa-miR-30b-5p were identified. KEGG analysis showed that PLXNA2 was enriched in the axon guidance. Pearson's correlation analysis showed that PLXNA2 and PGM3 were significantly negatively correlated with activated CD4 T cells, type 1 T helper cells and other immune cells. The TF-miRNA-mRNA regulatory network showed that FOXA1 was a TF for PLXNA2 and PGM3, and RUNX2 was a TF for PLXNA2. Moreover, FOXA1 and RUNX2 were also the target genes of hsa-miR-30b-5p. Hsa-miR-30b-5p identified from exosomes may be a miRNA marker specific to type 1 AIP and therefore has the potential to serve as a novel biomarker. •The hsa-miR-30b-5P identified from exosomes may be a miRNA marker specific to AIP.•The hsa-miR-30b-5P has the potential to serve as a novel biomarker for AIP diagnosis.•The MALAT1-hsa-miR-30b-5P-PLXNA2/PGM3 axis identified based on hsa-miR-30b-5P may play an important role in AIP.